Novel idea to monitor and measure blood hemoglobin noninvasively - Ar-Rawi, A.H.; Moghavvemi, Mahmoud; Ibrahim, W. (Academic Journals, 2010)
Measuring blood hematocrit noninvasively is reviewed in this paper. Although there is an inclination to measure the hematocrit by determining the bioelectrical impedance of the blood, in vitro experimental methods still remain practically inapplicable. The blood sample size is determined when blood samples are examined. Determining the impedance and volume of blood is the biggest challenge in measuring the hematocrit noninvasively without drawing a blood sample. Calculating the blood impedance in vivo requires developing an impedance measurement using a multi-frequency method and also calculating the change in pressure simultaneously during the heart's pulsatile cycle.